(untitled) (Journal of Computational Mathematics, 2018)
Based on the singular decomposition of 2×2 matrix an algorithm for reducing the matrix norm is presented. Under the optimal choice of the parameters the matrix B after transformation may be considered as "Locally normal", that is, the four corresponding elements of BB^T-B^TB are zero.